Challenge Implementation of General Principles of Good Government in Indonesian Government - Abdil Azizul Furqon; Ghiska Fajari; Wicipto Setiadi; Taufiqurrahman Syahuri (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
In the social field, there are development and change condition public will impact on existence anges to the order existing laws in the country. The more its height demands society so that the Government can organize with method transparent, accountable, more responsive to the needs and expectations that exist in society, create development theory principles general good government.​ This writing focuses on the challenges faced moment implementation principle the. With use normative juridical approach, author will study in a way regulation legislation. Based on results analysis writer, then can concluded that there is a number of a must challenge resolved, first balance strength in a democratic political system, second, systemic and independent supervision by existing state and social institutions with good, third, institution the law is not yet completely independent and impartial in carry out Justice law, fourth, quality source Power still human​ not enough in carry the trust given.